2001
DOI: 10.1093/clinchem/47.1.88
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Mycophenolic Acid Pharmacokinetic Parameters with Side Effects in Kidney Transplant Patients Treated with Mycophenolate Mofetil

Abstract: Background: Mycophenolate mofetil (MMF) is widely used in organ transplantation to prevent acute rejection. Because MMF can produce hematologic and/or gastrointestinal toxicity, therapeutic monitoring is becoming mandatory. This study was designed to investigate the relationship between the clinical events and the pharmacokinetics of mycophenolic acid (MPA) in adult renal transplantation. Methods: Thirty-one adult kidney recipients were prospectively included in the study. MPA pharmacokinetic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(67 citation statements)
references
References 16 publications
3
61
0
3
Order By: Relevance
“…15 High MPA AUCs have been associated with an increased risk of side effects, mostly leukopenia. 5 One might speculate that some of the side effects observed in patients treated with sirolimus, particularly in the immediate posttransplant period, such as leukopenia, 16 might be partly related to an overdosing of MPA.…”
Section: Discussionmentioning
confidence: 99%
“…15 High MPA AUCs have been associated with an increased risk of side effects, mostly leukopenia. 5 One might speculate that some of the side effects observed in patients treated with sirolimus, particularly in the immediate posttransplant period, such as leukopenia, 16 might be partly related to an overdosing of MPA.…”
Section: Discussionmentioning
confidence: 99%
“…For each patient, 2.6 mL of blood was withdrawn from a forearm vein into a heparin tube before drug administration and at 15 time points up to 48 h after dosing. The time points chosen were 0.25, 0.5, 0.75, 1, 1.5, 2, 2.5, 3,4,8,12,16,24,36, and 48 h post-dose. MPA and MPAG concentrations in plasma were determined by HPLC (sensitivity limit, 0.1 lg/mL) (data on file, Novartis Pharma AG).…”
Section: Ec-mps Vs Mmf Bioavailability Studymentioning
confidence: 99%
“…Reduction of the standard dose results in fewer sideeffects, although increases the risk of acute rejection. It has been shown that the area under the concentration-time curves (AUCs) vary widely in patients following the same MPA dosage [5].Therapeutic drug monitoring (TDM) might be useful for optimizing individual immunosuppressive therapy and improving allograft function [6][7][8][9][10]. In the French APOMYGRE study, titration of MMF dose according to plasma MPA concentrations resulted in an increased MPA exposure and a reduced incidence of acute rejection episodes without an increased risk of infections or haematological disorders [11].…”
Section: Introductionmentioning
confidence: 99%